Optimization of Sonotrode Ultrasonic-Assisted Extraction of Proanthocyanidins from Brewers’ Spent Grains - Beatriz Martín-García; Federica Pasini; Vito Verardo; Elixabet Díaz-de-Cerio; Urszula Tylewicz; Ana María Gómez-Caravaca; Maria Fiorenza Caboni (Antioxidants, 2019)
Brewing spent grains (BSGs) are the main by-product from breweries and they are rich of proanthocyanidins, among other phenolic compounds. However, literature on these compounds in BSGs is scarce. Thus, this research focuses on the establishment of ultrasound-assisted extraction of proanthocyanidin compounds in brewing spent grains using a sonotrode. To set the sonotrode extraction up, response surface methodology (RSM) was used to study the effects of three factors, namely, solvent composition, time of extraction, and ultrasound power. Qualitative and quantitative analyses of proanthocyanidin compounds were performed using HPLC coupled to fluorometric and mass spectrometer detectors. The highest content of proanthocyanidins was obtained using 80/20 acetone/water (v/v), 55 min, and 400 W. The established method allows the extraction of 1.01 mg/g dry weight (d.w.) of pronthocyanidins from BSGs; this value is more than two times higher than conventional extraction.